PERBANDINGAN EFEKTIVITAS APLIKASI SMART CONTINUITY OF CARE (MONSCA) DAN BUKU KIA TERHADAP DETEKSI DINI FAKTOR RISIKO KEHAMILAN - Ismayana; Werna Nontji; Syafruddin Syarif (Poltekkes Kemenkes Bandung, 2020)
The implementation of the Maternal and Child Health Program (MCH) aims to determine and increase the range and quality of MCH services effectively and efficiently. Antenatal care provides a platform for important health service functions, including health promotion, screening and diagnosis, and disease prevention so as to produce proper management during pregnancy, childbirth and the puerperium. The purpose of this study was to compare the effectiveness of the application of Smart Continuity of Care and the MCH handbook for early detection of pregnancy risk factors. The research method used was quasi experimental (pretest-posttes only control design). The population in this study were all midwives who worked in the Tanete Puskesmas and Bontobangun Puskesmas and all pregnant women who did antenatal checks at the Tanete Puskesmas and Bontobangun. In this study using a sample of midwives and pregnant women. The sampling technique in this study used purposive sampling. The number of samples was 36 people (18 intervention groups and 18 control groups). Determination of the number of samples of pregnant women using the Lemeshow formula, obtained samples of pregnant women as many as 44 people divided into two groups (22 intervention groups and 22 control groups). The results showed there were differences in effectiveness between early detection of pregnancy risk factors using the MCH handbook and using the Monsca application with p-value <(p = 0.05), in terms of convenience (p = 0,000), speed (p = 0.006), security (p = 0.005) and data accuracy (p = 0,000). So it can be concluded that the use of the Smart Continuity of Care application for early detection of risk factors for pregnancy is more effective without ignoring the use of the MCH book as a tool for MCH services.